Educational Relevance, Competencies, and Career Paths: A Tracer Study of Automotive Technology Graduates Towards Curriculum Design - Del Rosario Aquino, John Michael; Garcia, Jeffrey Navallo (Jurnal Pendidikan Progresif, 2023)
Abstract: Educational Relevance, Competencies, and Career Paths: A Tracer Study of Automotive Technology Graduates Towards Curriculum Design. Objective: this study explore the graduates of Automotive Technology from the year 2015 to 2020 which identifies the educational relevance, competencies, and career paths towards the designing of curriculum. Methods: The researchers employed descriptive research design and random sampling technique for collecting necessary information. A total of 113 respondents out of 164 graduates solicited responses through google form utilizing adapted survey questionnaire. Findings: The results revealed that most of the respondents agreed that their jobs related to their chosen courses. The graduates’ also acquired competencies or skills extremely important to work performance. Additionally, for productive and professional interactions, communication and interpersonal skills are stood up among others. In terms of career paths, graduates impacted by the skills they learned in college and how relevant they believe their course work to be to their jobs. Conclusion: Graduates who believe their education and employment are closely related may be more inclined to choose jobs. Keywords: tracer study, curriculum design, career paths, competencies, educational relevance.DOI: http://dx.doi.org/10.23960/jpp.v13.i3.202313